PERANCANGAN TAS ANAK MODULAR - HANS WILLIAM; Markus Hartono; Guguh Sujatmiko (Perpustakaan Universitas Surabaya, 2018)
Abstract - It is a daily necessity for people to do their activities. It shows a great significance when travelling. The use of bags can be applied in wide range of society, adults, teens and children. Children bring their bags to school, course, travel, and outing. The increasing demand on trend for children provides an opportunity to combine multiple bag products that goes with the modular trend becomes a feature to bags for children. The research methods used in this research are both qualitative and quantitative. The qualitative research is done by : analyze types of children bags, interviews with the children, parents, and experts, and observation on the things that the children brought. The quantitative research is done by observation on what type of bag that children brought on their activities : school, course, mall, and picnic. From the research we found children have more than 1 types of bag for their activities. The purpose of this project is to provide children a backpack that can be modified with ease. The backpack model can be modified just by opening the zipper. According to the research,